Regression-Based Classification of the Middle-Latency Auditory-Evoked Potentials in Vestibular Migraine and Concussion Patients with Dizziness - Carolina Beppi; Daniel Agostino; Antonella Palla; Nina Feddermann-Demont; Julia Dlugaiczyk; Dominik Straumann (Brain Sciences)
Background/Objectives: The auditory middle-latency responses (AMLRs) assess central sensory processing beyond the brainstem and serve as a measure of sensory gating. They have clinical relevance in the diagnosis of neurological conditions. In this study, magnitude and habituation of the AMLRs were tested for sensitivity and specificity in classifying dizzy patients with vestibular migraine (VM) and post-concussive syndrome. Methods: Twenty-three healthy individuals, 12 concussion and 26 VM patients were recruited. AMLR were recorded performing five blocks of 200 binaural click-stimulations at 60 dB sensation level with a repetition rate of 6.1 Hz. Reduction in P0, Na and Pa magnitudes between blocks was measured. Group classifications were performed through logistic and multiple regression. Results: Among healthy subjects, a consistent P0 and Na habituation can be observed. Concussed subjects show control-like Na habituation, despite a lower magnitude, while P0 habituation was negligible. VM patients showed poor habituation for all waves. Regression analyses suggest that P0 and Na better distinguish healthy subjects from neurological patients, whereas Pa best distinguishes concussion from VM patients. Conclusions: The results support that AMLR habituation can contribute to unraveling different mechanisms of dizziness due to concussion compared to VM, providing insights that can complement routine diagnostic assessments.